2001
DOI: 10.4141/s00-052
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia volatilization from soils fertilized with urea and varying rates of urease inhibitor NBPT

Abstract: . 2001. Ammonia volatilization from soils fertilized with urea and varying rates of urease inhibitor NBPT. Can. J. Soil Sci. 81: 239-246. Loss of N as ammonia (NH 3 ) from surface-applied urea fertilizer may be high if hydrolysis takes place at the soil surface. The urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT) may reduce NH 3 loss from urea by delaying hydrolysis. Field studies using surface chambers were conducted in 1996 and 1997 to compare the amount of NH 3 volatilized from surface applicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(100 citation statements)
references
References 21 publications
6
80
3
4
Order By: Relevance
“…16 The NBPT effectiveness is directly related to soil properties in which low concentration of this urease proinhibitor is needed to achieve the desired result in temperate soils while greater concentrations are required for tropical soils. [17][18][19][20] Additionally, NBPT is more efficient in neutral soils with limited organic matter. 17,21 Tropical soils exhibit organic matter and microbial biomass dynamics different from temperate soils.…”
Section: Introductionmentioning
confidence: 99%
“…16 The NBPT effectiveness is directly related to soil properties in which low concentration of this urease proinhibitor is needed to achieve the desired result in temperate soils while greater concentrations are required for tropical soils. [17][18][19][20] Additionally, NBPT is more efficient in neutral soils with limited organic matter. 17,21 Tropical soils exhibit organic matter and microbial biomass dynamics different from temperate soils.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature shows that across a range of crops and pastures, use of a urease inhibitor led to a 20% to 88% decrease in NH 3 volatilisation compared with urea (Watson et al 1990;Rawluk et al 2001;Turner et al 2010;Suter et al 2013). Due to the impacts on NH 3 volatilisation, it is expected that N 2 O emissions may increase relative to urea because of greater N in the system, but some studies have reported decreases in N 2 O with the urease inhibitor (Zaman et al 2009;Singh et al 2013;Ding et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is a need to improve the efficiency of urea-based fertilizers through new technologies and management approaches. One of the most promising approaches is to apply urea in combination with the urease inhibitor (N-(n-butyl) thiophosphoric triamide, nBTPT or NBPT) at low concentrations ranging from 0.01 to 0.5% (NBPT, w/w) (Watson and Miller, 1996;Rawluk et al, 2001;SanzCobena et al, 2008). Urease inhibitor (NBPT) is commercially available under the trade name of Agrotain.…”
Section: Introductionmentioning
confidence: 99%